Internal control gene VpEf1α in Vasconcellea pubescens (chamburo) - Cevallos Vilatuña, Tiffany Yiselle (2019)
The genes known as "housekeeping" control or regulate basic cellular processes and always remain activated, regardless of experimental conditions or between cells of different tissues. Vasconcellea pubescens, a species widely distributed in South America and belongs to the family Caricaceae just like papaya. First, primers for the EF1α gene were designed on basis of the genome of Carica papaya and Arabidopsis thaliana. Then, V. pubescens seedlings were subjected to three different temperatures. The quantification of the relative expression of the gene was performed by densitometry. Finally, the fragments obtained from RT-PCR were sequenced by second generation Sanger Sequencing and the bioinformatic analysis were performed with MEGA X while the statistical analysis were performed with RCommander. A 173 bp fragment was obtained which was named VpEF1α. The nucleotide sequence and the translation to amino acids turned out to be very similar when compared to known EF1α sequences from other plant species. From the phylogeny performed with the predicted protein, VpEF1α was grouped in a single clade with sequences of poplar, cocoa and papaya, all of them arboreal, while Arabidopsis and tobacco were located in another clade. The expression of the VpEF1α gene was similar in all the three temperatures evaluated, fulfilling the requirement that it does not change its expression at different experimental conditions. In this way an EF1 α type gene was described in V. pubescens (chamburo) that could be used as an internal control or housekeeping gene in future studies.